Performa Laju Pertumbuhan Ikan Bandeng (Chanos Chanos) yang Diberikan Pakan dengan Pengkayaan Probiotik - Linayati Linayati; Tegar Aji Prasetyo; Tri Yusufi Mardiana (JURNAL LITBANG KOTA PEKALONGAN, 2021)
Research objective to find out the optimal growth of milkfish seeds by giving probiotic with different doses.This research was conducted on Agust 15 th– September 14th, 2020 and is located at Marine and Brackish Water Laboratory, Faculty of Fisheries, Pekalongan University. The test fish used in this study was the 2,5 cm milkfish seeds obtained from fish farm’s from Pekalongan City. The research was carried out on a laboratory scale and the experimental design applied was completetely randomized design (CRD) which included 5 treatments and 3 replications, namely A (control), B (5 ml/kg of feed), C (10 ml/kg feed), D (15 ml/kg feed) and E (20 ml/kg feed). In order to find out the response ofthe growth of milk fish seeds to the addition of probiotic with different doses, a tukey test was performed. The highest growth of milkfish was obtained in treatment D that was 10,82gr, then followed by treatment C was 9,97gr, treatment B was 9,38gr, treatment E was 8,99gr and the lowest was in treatment A which was 7,73 gr. The results of the analysis of variance is known that the calculated F value is greater than the F table, which means the addition of probiotic with different doses has a very significant effect on the growth of milkfish seeds. Keywords: Probiotic, milkfish, growth